Gastropods as Bioindicators of Water Quality in Telindale Beach, Rote Tengah District, Rote Ndao Regency - Andriani Rafael; Yanti Daud; Theodora Sarlotha Nirmala Manu; Dewi Setiyowanto Gadi (Institut Pertanian Bogor, 2025)
Telindale Beach is part of the Central Rote Sub-district in the Rote Ndao Regency. The beach is also a seaside region with many community activities, including tourism, recreation, and sales. These activities have a significant impact on the health of aquatic ecosystems. The presence of pollutants in water might cause a decline in its quality. Gastropods are among the species that are sensitive to changes in water quality. This study sought to provide information on gastropod diversity as a bioindicator of water quality at Telindale Beach. This study was both descriptive and quantitative, with the location determined through purposive sampling. The line-transect approach was applied at three locations, each with a different substrate. The data were evaluated using diversity, uniformity, and dominance index techniques. The research revealed that the gastropods identified at the beach belonged to 13 families, 15 genera, and 19 species, with 112 individuals across all stations. The diversity index ranged from 0.27 to 2.33 (moderately contaminated), the uniformity index was 0.84-0.91 (high), and the dominance index was 0.12-0.31 (moderate). According to the species diversity index data, the waters near Telindale Beach were the most polluted. Keywords: bioindicator, gastropods, Telindale Beach